2016
DOI: 10.1002/jat.3346
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of single‐wall carbon nanotubes functionalized with polyethylene glycol in zebrafish (Danio rerio) embryos

Abstract: Single-wall carbon nanotubes functionalized with polyethylene glycol (SWCNT-PEG) are promising materials for biomedical applications such as diagnostic devices and controlled drug-release systems. However, several questions about their toxicological profile remain unanswered. Thus, the aim of this study was to investigate the action of SWCNT-PEG in Danio rerio zebrafish embryos at the molecular, physiological and morphological levels. The SWCNT used in this study were synthesized by the high-pressure carbon mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Wang et al (2016) found that bioaccumulation of MWCNTs was greater than that of SWCNTs and that embryos treated with SWCNTs presented severe malformations whereas embryos treated with MWCNTs presented normal development. In addition, Cheng et al (2007) and (Girardi et al 2017) reported a delay in the hatching rate of zebrafish embryos incubated with SWCNTs in a concentrationdependent manner. In contrast, working with a wide CNT concentration range that included the concentrations used by Cheng and Girardi, Bayat et al (2015) found no effects.…”
Section: Nanoparticles Carbon Nanotubesmentioning
confidence: 96%
See 1 more Smart Citation
“…Wang et al (2016) found that bioaccumulation of MWCNTs was greater than that of SWCNTs and that embryos treated with SWCNTs presented severe malformations whereas embryos treated with MWCNTs presented normal development. In addition, Cheng et al (2007) and (Girardi et al 2017) reported a delay in the hatching rate of zebrafish embryos incubated with SWCNTs in a concentrationdependent manner. In contrast, working with a wide CNT concentration range that included the concentrations used by Cheng and Girardi, Bayat et al (2015) found no effects.…”
Section: Nanoparticles Carbon Nanotubesmentioning
confidence: 96%
“…As mentioned above, another problem in toxicology studies of CNTs is the presence of impurities. Girardi et al (2017) established that the presence of metal impurities might be the principal cause of toxicity because the purification process is not able to remove them completely.…”
Section: Nanoparticles Carbon Nanotubesmentioning
confidence: 99%
“…120 However, a recent study by Girardi et al suggests that embryonically applied PEGylated SWCNTs did not cause any genotoxicity in zebrafish between the concentration values of 0.1 and 1 ppm. 121…”
Section: Genotoxicitymentioning
confidence: 99%
“…It is difficult to determine physiologically relevant cytotoxicity due to difference in toxicity parameters during the study by different groups. To understand the toxic effect several biological models includes cell lines, aquatic embryonic zebrafish (Danio rerio), and whole-animal tests such as rodents (mice/rat) (Girardi et al 2017;Griffitt et al 2007).…”
Section: Toxicity Of Nanomaterialsmentioning
confidence: 99%